2013
DOI: 10.1136/bjophthalmol-2012-302227
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcomes of primary trabeculectomy in diabetic patients with primary open angle glaucoma

Abstract: POAG patients with DM without retinopathy undergoing primary trabeculectomy with MMC do not achieve the same long-term IOP control and may have a lower long-term surgical survival rate compared with patients without DM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
13
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 18 publications
2
13
0
2
Order By: Relevance
“…The surgical outcomes have been extensively studied for classic trabeculectomy and argon laser trabeculoplasty (ALT), but the literature is sparse when we look for newer procedures, such as the nonpenetrating sclerectomy or drainage devices. 30 - 33 …”
Section: Is Diabetes a Risk Factor To Glaucoma Surgical Outcomes?mentioning
confidence: 99%
See 1 more Smart Citation
“…The surgical outcomes have been extensively studied for classic trabeculectomy and argon laser trabeculoplasty (ALT), but the literature is sparse when we look for newer procedures, such as the nonpenetrating sclerectomy or drainage devices. 30 - 33 …”
Section: Is Diabetes a Risk Factor To Glaucoma Surgical Outcomes?mentioning
confidence: 99%
“…Literature has a huge diversity of articles considering these conclusions in varied group of patients, such as proliferative diabetic retinopathy, no proliferative diabetic retinopathy in progression or diabetes without retinopathy. 30 - 33 …”
Section: Is Diabetes a Risk Factor To Glaucoma Surgical Outcomes?mentioning
confidence: 99%
“…These contradictory findings, taken together with the equivocal findings of Law et al ,4 may indicate that diabetes is not a major risk factor for trabeculectomy failure on the same order as prior failed filtering surgery or neovascular glaucoma; but nonetheless, it should be taken into consideration at the time of surgery, for example, when the surgeon is deciding whether to apply mitomycin for the usual amount of time, versus an increased application time in order to offset a history of diabetes, even without retinopathy. Further comparative and/or prospective reports on filtering surgery success in diabetics, with documentation of blood glucose control and retinopathy status, and using the longer mitomycin application times that are more typically used by many glaucoma surgeons are welcome, given the impending wave of diabetic patients that awaits us in the future.…”
mentioning
confidence: 90%
“…Law and colleagues4 report on a case–control study of diabetic eyes without retinopathy that underwent primary trabeculectomy by the same two surgeons. Both groups received adjunctive intraoperative mitomycin at the time of surgery for a relatively short duration (average about 1 min—about half the dose typically used by the American Glaucoma Society members in primary trabeculectomy) 5.…”
mentioning
confidence: 99%
“…However, published data were mainly focused on trabeculectomy in diabetic eyes with proliferative disease or with different stages of diabetic retinopathy [4–6]. Law et al reported the long-term outcomes of primary trabeculectomy with mitomycin-C (MMC) in diabetic patients without retinopathy with primary open-angle glaucoma (POAG) [7]. The result indicated that POAG patients with DM without retinopathy undergoing primary trabeculectomy may have a lower long-term surgical survival rate compared with patients without DM.…”
Section: Introductionmentioning
confidence: 99%